Dollar-Cost Averaging: An Investigation - FANG, Wei (2007)
Dollar-cost Averaging (DCA) is a common and useful systematic investment strategy for mutual fund managers, private investors, financial analysts and retirement planners. The issue of performance effectiveness of DCA is greatly controversial among academics and professionals. As a popularly recommended investment strategy, DCA is recognized as a risk reduction strategy; however, the advantage was claimed as the expense of generating higher returns.